2003
DOI: 10.1291/hypres.26.s121
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Adrenomedullin in Heart Failure

Abstract: Many neurohumoral factors participate in the pathophysiology of heart failure, and adrenomedullin (AM) may be involved in their derangement. This work reviews the accumulating evidence in support of a compensatory role of AM in heart failure, and describes the possible mechanisms of this role. It has been established that plasma AM levels are increased in patients with heart failure in proportion to the severity of the disease. Furthermore, recent studies suggest that plasma AM level is an independent prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…3,[27][28][29] The mechanism by which AM exerts its effects on cardiomyocytes is not fully understood. A previous report showed that AM signaling depends on the combination of CRLR (calcitonin receptor-like receptor) and RAMP2 (receptor activity- modifying proteins), resulting in activation of the AM receptor.…”
Section: Discussionmentioning
confidence: 99%
“…3,[27][28][29] The mechanism by which AM exerts its effects on cardiomyocytes is not fully understood. A previous report showed that AM signaling depends on the combination of CRLR (calcitonin receptor-like receptor) and RAMP2 (receptor activity- modifying proteins), resulting in activation of the AM receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous AM plays a role in protecting the heart and kidneys from damage during cardiovascular stresses such as hypertension and its associated cardiac hypertrophy, myocardial infarction, heart failure, and atherosclerosis (18,19). Thus, comparisons between male mice with genetically reduced levels of AM (AM ϩ/Ϫ ) and wild-type mice (AM ϩ/ϩ ) have demonstrated that the reduced level of endogenous AM increases the damage to heart and renal tissue caused by aortic banding (20), angiotensin II infusion (20,21), bilateral renal artery clamping (22), and atherosclerosis (23).…”
mentioning
confidence: 99%
“…Adrenomedullin is now recognized as a key peptide in many tissues in many species that serves as a coordinating tissue survival factor in many species during decompensating stress [6,7,42]. Examples of activity include its capacity to ameliorate regional ischemic events and blood shunting during sepsis by maintaining local tissue oxygen perfusion and blood flow [43], reducing tissue necrosis and apoptosis through AM/AM-BP complex-augmented production of anti-apoptotic BCL-2 cascade factors and concomitantly decreased pro-apoptotic Bax gene expression [44], effects on pancreatic hormone secretion and localized tissue metabolic responses to pancreatic hormones [13,29,30], interactions with the LPS-TNF-␣-nitric oxide cascade [12,13,38], and its effects to neutralize growth and pathogenic activities of both Gram-negative and Gram-positive [8][9][10] bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the activity of AM-BP as complement factor-H (responsible cofactor for the factor I-dependant cleaving of complement C3B) is increased when AM is bound [17] suggesting that aspects of the innate complement cascade within the mammary gland [49] are also modulated by AM. Furthermore, increased beneficial clinical outcome (decreased morbidity and mortality) recently has been attributed to the use of an AM/AM-BP complex as an intervention strategy to limit the complicating effects of sepsis and hypovolumic shock on progression into multiple organ failure [19,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%